EARLY WEIGHT LOSS OUTCOMES AND GLUCOSE METABOLISM PARAMETERS AFTER BANDED VERSUS NON-BANDED ONE ANASTOMOSIS GASTRIC BYPASS: A PROSPECTIVE RANDOMIZED TRIAL - CAZZO,Everton (2019)
ABSTRACT BACKGROUND: The influence of the placement of a band on the outcomes of one anastomosis gastric bypass (OAGB) has not been appropriately studied yet. OBJECTIVE: To compare early weight loss and glucose metabolism parameters following banded versus non-banded OAGB. METHODS: A prospective randomized study, which evaluated 20 morbidly obese individuals who underwent banded and non-banded OAGB and were followed-up for three months. Weight loss (percentage of excess weight loss - %EWL and percentage of body mass index loss - %BMIL) and glucose metabolism outcomes (glucose, insulin and homeostasis model assessment - HOMA) were compared. RESULTS: The banded group presented a significantly higher %EWL at one month (29.6±5.5% vs 17.2±3.4%; P<0.0001) and two months post-surgery (46±7% vs 34.2±9%; P=0.004544), as well as a significantly higher %BMIL at one month (9.7±1.1% vs 5.8±0.8%; P<0.0001), two months (15±1.4% vs 11.5±2.1; P=0.000248), and three months (18.8±1.8% vs 15.7±3.2%; P=0.016637). At three months, banded OAGB led to significant decreases of insulin (14.4±4.3 vs 7.6±1.9; P=0.00044) and HOMA (3.1±1.1 vs 1.5±0.4; P=0.00044), whereas non-banded OAGB also led to significant decreases of insulin (14.8±7.6 vs 7.8±3.1; P=0.006) and HOMA (3.2±1.9 vs 1.6±0.8; P=0.0041). The percent variation of HOMA did not significantly differ between banded and non-banded OAGB (P=0.62414); overall, the percent variation of HOMA was not correlated with %EWL (P=0.96988) or %BMIL (P=0.82299). CONCLUSION: Banded OAGB led to a higher early weight loss than the standard technique. Banded and non-banded OAGB led to improvements in insulin resistance regardless of weight loss.